Composite catalyst as well as preparation method and application thereof

By using a bimetallic cyanide catalyst to form a stable cluster structure with polyethyleneimine as a catalyst, a carbon dioxide-based copolymer with a microcrosslinked structure was prepared, which solved the problem of poor thermal stability of PPC in the prior art and achieved significant results Improved heat resistance.

CN119390974APending Publication Date: 2025-02-07SHANGHAI HUAFON NEW MATERIAL R&D TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411516877.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to control the crosslinking degree of polymers when preparing carbon dioxide-based copolymers, resulting in poor thermal stability of PPC and prone to excessive crosslinking or insufficient crosslinking.

Method used

A bimetallic cyanide catalyst and polyethyleneimine are used to form a stable cluster structure as a catalyst. Through this composite catalyst, a micro-crosslinked structure is formed when the carbon dioxide-based copolymer is prepared, thereby improving its thermal stability.

Benefits of technology

By forming a micro-crosslinking structure, the thermal stability of the carbon dioxide-based copolymer is significantly improved, excessive cross-linking or insufficient cross-linking is avoided, and its heat resistance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390974A_ABST
    Figure CN119390974A_ABST
Patent Text Reader

Abstract

The invention provides a composite catalyst and a preparation method and application thereof, the composite catalyst comprises a double metal cyanide catalyst and polyethyleneimine, and the double metal cyanide catalyst and the polyethyleneimine are combined in a stable cluster form; meanwhile, in the preparation process of the composite catalyst, Zn salt is prepared into a component A, a double-metal cyanide catalyst precursor and polyethyleneimine are prepared into a component B, and when the component A and the component B are mixed, the double-metal cyanide catalyst precursor can be converted into a double-metal cyanide catalyst; meanwhile, the obtained double-metal cyanide catalyst and polyethyleneimine are induced to be complexed to form a cluster, so that the obtained composite catalyst has excellent thermal stability, and when the composite catalyst is further used as a catalyst for preparing the carbon dioxide-based copolymer, a micro-crosslinking structure can be formed in the carbon dioxide-based copolymer; therefore, the thermal stability of the carbon dioxide-based copolymer is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a composite catalyst and a preparation method and application thereof. Background Art

[0002] Carbon dioxide (CO2) is a common greenhouse gas. With the rapid development of industrial levels in various countries, the carbon dioxide content in the air has increased, and the greenhouse effect has continued to intensify. Now the carbon dioxide content in the air has reached the highest value since the birth of mankind. Therefore, controlling carbon dioxide emissions has attracted widespread attention, and the fixation and utilization of carbon dioxide has also become a current research hotspot.

[0003] In 1969, Professor Inoue of Japan used diethyl zinc as a catalyst for the first time to synthesize polypropylene carbonate (PPC) from carbon dioxide and epoxides. This method not only fixes carbon and reduces carbon emissions, but the resulting PPC also has the advantages of being low-priced and biodegradable. Therefore, after nearly 50 years of research, PPC has become one of the most industrially valuable varieties of all carbon dioxide copolymers.

[0004] Double metal cyanide (DMC) catalyst is the most commonly used catalyst for preparing PPC. Compared with other catalysts, double metal cyanide catalyst has the advantages of high catalytic efficiency, colorless appearance of the obtained PPC and no need to remove the catalyst. However, the PPC obtained by using DMC as a catalyst has a high polyether content and poor thermal stability. Its 5% thermal decomposition temperature is about 260°C, which limits the subsequent processing and use of PPC.

[0005] It is known that the heat resistance of polymers can be improved by cross-linking polymers. The prior art can adjust the polymer to produce a certain degree of cross-linking by adding multifunctional small molecule monomers (refer to "Architecting Branch Structure in Terpolymer of CO2, Propylene Oxide and Phthalic Anhydride: An Enhancement in Thermal and Mechanical Performances"); however, when adding multifunctional small molecule monomers such as pyromellitic anhydride to the PPC polymerization system catalyzed by a double metal cyanide catalyst, there is a problem that it is very difficult to control the degree of cross-linking of the polymer, which can easily lead to excessive or insufficient cross-linking of PPC, affecting its physical and chemical properties.

[0006] Therefore, in view of the above technical problems, developing a composite catalyst that can enable carbon dioxide-based copolymers to produce a controllable micro-crosslinked structure is a major unsolved problem in industrial production in this field. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a composite catalyst and a preparation method and application thereof. When the composite catalyst is used as a catalyst to prepare a carbon dioxide-based copolymer, the obtained carbon dioxide-based copolymer can form a micro-crosslinked structure, thereby greatly improving the thermal stability of the carbon dioxide-based copolymer.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a composite catalyst, the composite catalyst comprising a double metal cyanide catalyst and polyethyleneimine, and the two are combined in the form of a stable cluster;

[0010] The double metal cyanide catalyst contains Zn element.

[0011] The inventors of the present invention creatively discovered during the research process that after the double metal cyanide catalyst and polyethyleneimine are complexed to form stable clusters during the preparation process, when used for catalytic preparation of carbon dioxide-based copolymers (PPC), the active sites of each double metal cyanide catalyst in the formed cluster can be used as the starting point for chain growth, and a physical micro-crosslinked structure can be obtained at this time. Since the structure of the formed cluster is still very stable at the thermal decomposition temperature of PPC, the PPC with a micro-crosslinked structure prepared by using the catalyst is also very stable and has excellent heat resistance. After complexation, in the process of forming a stable cluster by complexation of the double metal cyanide catalyst and polyethyleneimine, part of the active sites on the catalyst are occupied by polyethyleneimine to form a stable cluster structure; when the cluster structure increases, some double metal cyanide catalysts are completely wrapped by the molecular chains of polyethyleneimine, and these wrapped active sites cannot trigger the reaction, while the active sites on the surface play a role in triggering chain growth. Therefore, even if a large amount of double metal cyanide catalysts are complexed in the clusters, the resulting PPC will not be over-crosslinked; however, when there is too much polyethyleneimine and the cluster size is too large, a large number of active sites will be encapsulated, resulting in the weakening of the activity of the resulting composite catalyst.

[0012] Specifically, the structural schematic diagram of PPC prepared by using the composite catalyst provided by the present invention and using a conventional double metal cyanide catalyst is as follows: Figure 1 shown.

[0013] In addition, the inventors of the present invention have also found through research that the non-complexing addition of a simple mixture of a double metal cyanide catalyst and polyethyleneimine does not have the above-mentioned effect and cannot obtain a PPC with a physical micro-crosslinked structure because the obtained PPC will only polymerize on the surface of the double metal cyanide catalyst, and the addition of polyethyleneimine has a certain effect on the activity of the double metal cyanide catalyst, but it is not significant.

[0014] In the present invention, the "stable cluster" refers to the cluster (i.e., the composite catalyst) after heat treatment at 300°C for 2h. 50 The particle size change rate is ≤5% (e.g., 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5% or 1%), that is, the original D of the composite catalyst is compared with the original D of the composite catalyst. 50 Particle size and D after heat treatment 50 The particle size change rate determines whether the composite catalyst has formed a stable cluster, which can be calculated according to the following formula:

[0015] D 50 Particle size change rate (%) = (the original D 50 Particle size-D of composite catalyst after heat treatment 50 Particle size) / Original D of composite catalyst 50 Particle size × 100%;

[0016] Among them, the original D 50 Particle size and D after heat treatment 50 The particle size can be measured by Dandong Better Instruments BT-9300S laser particle size analyzer; the specific test method is: disperse the composite catalyst into ethanol solvent, the concentration of the obtained composite catalyst dispersion is 2mg / mL, ultrasonic for 5min, and the D 50 Particle size data.

[0017] In the present invention, the specific type of the double metal cyanide catalyst is not particularly limited, and any double metal cyanide catalyst known to the public that can be used to catalyze PPC polymerization can be used; illustratively, the double metal cyanide catalyst includes a Zn / Co double metal cyanide catalyst, a Zn / Fe double metal cyanide catalyst, a Zn / Ni double metal cyanide catalyst or a Zn / Cr double metal cyanide catalyst, etc.

[0018] Preferably, the mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine is (20-100):1, for example, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1 or 100:1.

[0019] In the present invention, the mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine will directly affect the complexing effect of the two, thereby affecting the particle size of the composite catalyst clusters obtained by complexing, and ultimately affecting the micro-crosslinked structure of the prepared PPC; on the one hand, if the mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine is higher than 100:1, the particle size of the composite catalyst clusters formed by the complexing of polyethyleneimine and the double metal cyanide catalyst will be too small, thereby resulting in a low PPC content in the subsequent micro-crosslinked structure, and the thermal stability of the PPC finally prepared will not be significantly improved; on the other hand, if the mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine is lower than 20:1, the particle size of the composite catalyst clusters formed by complexing will be too large, further resulting in relatively more double metal cyanide catalysts in the composite catalyst being wrapped inside the clusters, and this part of the wrapped double metal cyanide catalyst is difficult to contact with the monomer during polymerization and cannot catalyze the reaction, thereby slowing down the polymerization reaction or even causing the polymerization to fail.

[0020] In the present invention, the "mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine" is determined by the following method:

[0021] (1) Test the mass percentage of Zn element in the composite catalyst (W Zn ): Take 1g of the composite catalyst and determine the mass percentage of Zn element in it by elemental analysis, which is recorded as w Zn ;

[0022] (2) Test the mass percentage of N element from polyethyleneimine in the composite catalyst (W N1 ): Take 1g of the composite catalyst, and determine the total mass percentage of the N element and the mass percentage of another metal element other than Zn from the double metal cyanide catalyst by elemental analysis, which are recorded as W N总 and W M , then W N1 Calculated according to the following formula:

[0023]

[0024] Among them, W N1 It represents the mass percentage of N element from polyethyleneimine in the composite catalyst, in %;

[0025] W N总 It indicates the total mass percentage of N element in the composite catalyst, in %;

[0026] W MIt indicates the mass percentage of another metal element (such as Co, Fe, Ni or Cr, etc.) in the double metal cyanide catalyst other than Zn in the composite catalyst, in %;

[0027] M represents the mass number of another metal element (such as Co, Fe, Ni or Cr, etc.) in the composite catalyst except Zn from the double metal cyanide catalyst;

[0028] 14 represents the mass number of element N;

[0029] The n value depends on the valence state of another metal element other than Zn in the double metal cyanide catalyst. For example, when the other metal element is Co, the n value is 6; when the other metal element is Fe, the n value is 6; when the other metal element is Ni, the n value is 4; when the other metal element is Cr, the n value is 4;

[0030] (3) The mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine is equal to the mass ratio of the W obtained in the above step (1). Zn :W N1 ;

[0031] In the above tests, elemental analysis was performed using a Zeiss Sigma 300 field emission scanning electron microscope with an accelerating voltage of 5 kV.

[0032] Preferably, the D of the composite catalyst 50 The particle size is 12 to 50 μm, for example, 12 μm, 18 μm, 20 μm, 30 μm, 40 μm or 50 μm.

[0033] In the present invention, the particle size of the composite catalyst will directly affect the catalytic effect of the composite catalyst in the PPC polymerization process. 50 The particle size is less than 12 μm, and the PPC micro-crosslinking degree obtained by the obtained composite catalyst when catalyzing PPC polymerization is insufficient, which leads to poor thermal stability; when the D 50 The particle size is greater than 50 μm, which results in the particle size of the composite catalyst clusters formed by complexation being too large, further resulting in relatively more catalysts in the obtained composite catalyst being encapsulated inside the clusters. This part of the encapsulated catalyst is difficult to contact with the monomer during polymerization and cannot catalyze the reaction, which in turn causes the polymerization reaction to slow down or even fail.

[0034] Preferably, the number average molecular weight of the polyethyleneimine is 3000-10000, for example, 3000, 4000, 5000, 6000, 7000, 8000 or 10000.

[0035] In the present invention, the number average molecular weight of the polyethyleneimine will also directly affect its complexing ability with the initiation points on the double metal cyanide catalyst, and further affect the density of cross-linking points formed between the polyethyleneimine and the double metal cyanide catalyst; on the one hand, if the number average molecular weight of the polyethyleneimine is lower than 3000, it is easy to cause too few sites for the polyethyleneimine to complex with the double metal cyanide catalyst, and further cause the physical cross-linking points formed by the polyethyleneimine and the double metal cyanide catalyst to have poor thermal stability, resulting in poor high temperature stability of the composite catalyst obtained by complexation, and further leading to the thermal stability of PPC; on the other hand, if the number average molecular weight of the polyethyleneimine is higher than 10000, it is easy to cause the initiation sites of the double metal cyanide catalyst to be occupied too much by the polyethyleneimine, making it difficult to initiate the PPC polymerization reaction, and even leading to polymerization failure.

[0036] In a second aspect, the present invention provides a method for preparing a composite catalyst, the preparation method comprising the following steps:

[0037] (1) mixing Zn salt, organic ligand and tert-butyl alcohol in water to obtain component A;

[0038] Mixing a double metal cyanide catalyst precursor and polyethyleneimine in water to obtain a component B;

[0039] (2) Adding the obtained component B to the component A for mixing, aging, washing and drying, to obtain the composite catalyst.

[0040] The preparation method of the composite catalyst provided by the present invention comprises the following steps: firstly preparing a component A containing a Zn salt, an organic ligand and tert-butyl alcohol, wherein the tert-butyl alcohol serves as a reaction solvent and an organic ligand; and further preparing a component B containing a double metal cyanide catalyst precursor and polyethyleneimine; then adding the component B into the component A for mixing, and subjecting the mixture to aging, during which the Zn salt and the double metal cyanide catalyst precursor can react to form a double metal cyanide catalyst containing Zn metal, i.e., obtaining a double metal cyanide catalyst precipitate, and in this process, the double metal cyanide catalyst obtained by the reaction can be complexed with polyethyleneimine to form a catalyst cluster of relatively large size; and finally, washing and drying can be performed to obtain the composite catalyst.

[0041] In the preparation method of the composite catalyst provided by the present invention, component A containing Zn salt, organic ligand and tert-butyl alcohol is first prepared, wherein the preparation method of component A is a known technology, which is the same as the conventional method for preparing double metal cyanide catalysts.

[0042] Preferably, the mass ratio of the Zn salt to tert-butanol is (3-30):100, for example, 3:100, 6:100, 9:100, 10:100, 12:100, 14:100, 16:100, 18:100, 20:100, 22:100, 24:100, 26:100, 28:100 or 30:100, etc.

[0043] Preferably, the mass ratio of the Zn salt to the organic ligand is 1:(0.5-10), for example, 1:0.5, 1:1, 1:2, 1:4, 1:6, 1:8 or 1:10.

[0044] Among them, the Zn salt, organic ligand and tert-butanol are all well-known raw materials for preparing double metal cyanide catalysts. In the present invention, the specific types of the Zn salt and organic ligand are not particularly limited, and any Zn salt and organic ligand known to the public that can be used to prepare double metal cyanide catalysts can be used; illustratively, the Zn salt includes zinc chloride, zinc sulfate or zinc bromide; the organic ligand includes tert-butanol, tetrahydrofuran, propylene glycol dimethyl ether, dioxane, tert-butyl ether, ethylene glycol dimethyl ether or diethylene glycol dimethyl ether.

[0045] Preferably, the total mass percentage of Zn salt in component A is 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0046] Preferably, the number average molecular weight of the polyethyleneimine is 3000-10000, for example, 3000, 4000, 5000, 6000, 7000, 8000 or 10000.

[0047] Preferably, the mass ratio of the double metal cyanide catalyst precursor to polyethyleneimine is (10-100):1, such as 10:1, 20:1, 40:1, 60:1, 80:1 or 100:1.

[0048] In the present invention, compared with the reactant double metal cyanide catalyst precursor of component B, the reactant Zn salt of component A is relatively excessive, as long as it is ensured that no double metal cyanide catalyst precursor is contained in the component after sufficient aging (reaction) (<100ppm is considered as no content), that is, all the double metal cyanide catalyst precursor in component B is combined with Zn and precipitated.

[0049] Since the Zn salt in component A is excessive, the amount of Zn salt that actually enters the composite catalyst by reacting with the double metal cyanide catalyst precursor in component B and precipitating is related to the amount of the double metal cyanide catalyst precursor in component B. When the mass ratio of the double metal cyanide catalyst precursor to polyethyleneimine is too large, it is easy to cause the D of the obtained composite catalyst to increase.50 The particle size will be less than 12 μm; if the mass ratio is too small, the D 50 The particle size will be greater than 50 μm.

[0050] In the present invention, there is no special requirement for the type of the double metal cyanide catalyst precursor, and any double metal cyanide catalyst precursor known to the public that can be used to prepare a double metal cyanide catalyst can be used; illustratively, the double metal cyanide catalyst precursor includes potassium hexacyanocobaltate, potassium hexacyanoferrate, potassium tetracyanonickelate or potassium tetracyanochromate, etc.

[0051] Preferably, the mass percentage of polyethyleneimine in the component B is 0.1-5%, for example, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 2%, 3%, 4%, 5%, etc.

[0052] Preferably, the time for adding the component B obtained in step (1) to the component A for mixing is ≥1 min, such as 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc.; there is no more specific mechanism research at present, but it is found that the significantly insufficient time for adding will also directly affect the particle size of the obtained composite catalyst, and further affect the complexing effect between the double metal cyanide catalyst and the polyethyleneimine in the composite catalyst; regardless of the mixing ratio of the components A and B, if the addition time is less than 1 min, the D of the obtained composite catalyst will be 50 The particle size will be greater than 50 μm, which will lead to a slowdown in the polymerization reaction or even termination of the polymerization.

[0053] In the present invention, there is no limitation on the aging temperature and time, as long as the mixed solution does not contain double metal cyanide catalyst precursor (<100 ppm is considered as no double metal cyanide catalyst precursor), that is, all double metal cyanide catalyst precursor in component B is combined with Zn and precipitated.

[0054] Exemplarily, the aging temperature is 30-70°C, such as 30°C, 40°C, 50°C, 60°C or 70°C.

[0055] Exemplarily, the aging time is 1 to 8 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.

[0056] In a third aspect, the present invention provides a slightly cross-linked carbon dioxide-based copolymer, which is prepared using at least one of the composite catalysts described in the first aspect or the composite catalysts prepared by the preparation method described in the second aspect as a catalyst.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] The composite catalyst provided by the present invention comprises a double metal cyanide catalyst and polyethyleneimine, and the two are combined in the form of a stable cluster; meanwhile, in the process of preparing the composite catalyst, a Zn salt is configured as component A, and a double metal cyanide catalyst precursor and polyethyleneimine are configured as component B; when the components A and B are mixed, the double metal cyanide catalyst precursor and the Zn salt react to be converted into a double metal cyanide catalyst, and at the same time induce the obtained double metal cyanide catalyst and the polyethyleneimine in the component A to complex to form a cluster, so that the obtained composite catalyst itself has excellent thermal stability; when further used as a catalyst for preparing a carbon dioxide-based copolymer, a micro-crosslinking structure can be formed inside the obtained carbon dioxide-based copolymer, thereby greatly improving the thermal stability of the carbon dioxide-based copolymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 A schematic diagram of the structure of PPC prepared by using the composite catalyst provided by the present invention and using a double metal cyanide catalyst;

[0060] Figure 2 A scanning electron microscope image of the composite catalyst provided in Example 5;

[0061] Figure 3 This is a scanning electron microscope image of the double metal cyanide catalyst provided in Comparative Example 1.

[0062] Terminology

[0063] The "stable cluster" means that the particle size of the composite catalyst cluster is stable, and the double metal cyanide catalyst and polyethyleneimine in the cluster can still be stably complexed together at high temperature, and after high temperature treatment (treated at 300°C for 2h), the cluster will not be disintegrated due to violent Brownian motion. The particle size change rate of the cluster before and after high temperature treatment is ≤5%, which is regarded as a stable cluster. DETAILED DESCRIPTION

[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0065] Unless otherwise specified, the raw materials involved in the following specific embodiments are all conventional materials in the art and can be purchased from commercial products.

[0066] Example 1

[0067] A composite catalyst comprises a double metal cyanide catalyst and polyethyleneimine, and the two are combined in a stable cluster form;

[0068] Among them, D of the composite catalyst at room temperature 50 The particle size is 12 μm, and the D 50 The particle size is 12 μm, D 50 The particle size change rate is 0%, and the particle size of the clusters is stable at high temperatures;

[0069] The mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine (number average molecular weight of 10000) is 100:1;

[0070] The double metal cyanide catalyst is a Zn / Co double metal cyanide catalyst;

[0071] The preparation method of the composite catalyst provided in this embodiment comprises the following steps:

[0072] (1) mixing zinc chloride, ethylene glycol dimethyl ether and tert-butyl alcohol in deionized water, wherein the mass ratio of zinc chloride to tert-butyl alcohol is 3:100, and the mass ratio of zinc chloride to ethylene glycol dimethyl ether is 1:0.5, to obtain a component A having a weight percentage content of 1% of Zn salt;

[0073] Mixing the precursor potassium hexacyanocobaltate and polyethyleneimine (number average molecular weight of 10,000) in deionized water, wherein the mass ratio of potassium hexacyanocobaltate to polyethyleneimine is 180:1, and the amount of solvent is matched according to the mass percentage of polyethyleneimine of 0.1%, to obtain component B;

[0074] (2) adding component B obtained in step (1) to component A and mixing them for 10 minutes to obtain an intermediate slurry;

[0075] (3) The intermediate slurry in step (2) is aged at 40° C. for 2 h to make it free of Co, and then washed and dried in sequence to obtain the composite catalyst.

[0076] Example 2

[0077] A composite catalyst comprises a double metal cyanide catalyst and polyethyleneimine, and the two are combined in a stable cluster form;

[0078] Among them, D of the composite catalyst at room temperature 50 The particle size is 41 μm. After high temperature treatment at 300 °C for 2 h, the D 50 The particle size is 40 μm, D 50 The particle size change rate is 2%, and the particle size of the clusters is stable at high temperatures;

[0079] The mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine (number average molecular weight of 8500) is 33:1;

[0080] The double metal cyanide catalyst is a Zn / Fe double metal cyanide catalyst;

[0081] The preparation method of the composite catalyst provided in this embodiment comprises the following steps:

[0082] (1) mixing zinc chloride, glycerol dimethyl ether and tert-butyl alcohol in deionized water, wherein the mass ratio of zinc chloride to tert-butyl alcohol is 20:100, and the mass ratio of zinc chloride to glycerol dimethyl ether is 1:1, to obtain a component A having a Zn salt content of 8% by mass;

[0083] Precursors potassium hexacyanoferrate and polyethyleneimine (number average molecular weight of 8500) were mixed in deionized water, wherein the mass ratio of potassium hexacyanoferrate to polyethyleneimine was 55:1, and the amount of solvent was matched according to the mass percentage of polyethyleneimine of 3%, to obtain component B;

[0084] (2) adding component B obtained in step (1) to component A and mixing for 3 minutes to obtain an intermediate slurry;

[0085] (3) The intermediate slurry in step (2) is aged at 40° C. for 2 h to make it free of Fe, and then washed and dried in sequence to obtain the composite catalyst.

[0086] Example 3

[0087] A composite catalyst comprises a double metal cyanide catalyst and polyethyleneimine, and the two are combined in a stable cluster form;

[0088] Among them, D of the composite catalyst at room temperature 50 The particle size is 29 μm. The particle size of D5 after high temperature treatment at 300 °C for 2 h is 28 μm. 50 The particle size change rate is 3%, and the particle size of the clusters is stable at high temperatures;

[0089] The mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine (number average molecular weight of 6000) is 52:1;

[0090] The double metal cyanide catalyst is a Zn / Ni double metal cyanide catalyst;

[0091] The preparation method of the composite catalyst provided in this embodiment comprises the following steps:

[0092] (1) mixing zinc chloride, tetrahydrofuran and tert-butanol in deionized water, wherein the mass ratio of zinc chloride to tert-butanol is 10:100, and the mass ratio of zinc chloride to tetrahydrofuran is 1:2, to obtain a component A having a Zn salt content of 6% by mass;

[0093] Precursors potassium tetracyanonitric acid and polyethyleneimine (number average molecular weight 6000) were mixed in deionized water, the mass ratio of potassium tetracyanonitric acid to polyethyleneimine was 90:1, and the amount of solvent was matched according to the mass percentage of polyethyleneimine 2%, to obtain component B;

[0094] (2) adding component B obtained in step (1) to component A and mixing them for 4 minutes to obtain an intermediate slurry;

[0095] (3) The intermediate slurry in step (2) is aged at 40° C. for 2 h to make it free of Ni, and then washed and dried in sequence to obtain the composite catalyst.

[0096] Example 4

[0097] A composite catalyst comprises a double metal cyanide catalyst and polyethyleneimine, and the two are combined in a stable cluster form;

[0098] Among them, D of the composite catalyst at room temperature 50 The particle size is 22 μm, and the D 50 The particle size is 21 μm, D 50 The particle size change rate is 5%, and the particle size of the clusters is stable at high temperatures;

[0099] The mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine (number average molecular weight of 3000) is 79:1;

[0100] The double metal cyanide catalyst is a Zn / Co double metal cyanide catalyst;

[0101] The preparation method of the composite catalyst provided in this embodiment comprises the following steps:

[0102] (1) mixing zinc chloride, dioxane and tert-butyl alcohol in deionized water, wherein the mass ratio of zinc chloride to tert-butyl alcohol is 15:100, and the mass ratio of zinc chloride to dioxane is 1:5, to obtain a component A having a Zn salt content of 2% by mass;

[0103] Precursors potassium hexacyanocobaltate and polyethyleneimine (number average molecular weight of 3000) were mixed in deionized water, the mass ratio of potassium tetracyanonickelate to polyethyleneimine was 145:1, and the amount of solvent was matched according to the mass percentage of polyethyleneimine of 1%, to obtain component B;

[0104] (2) adding component B obtained in step (1) to component A and mixing them for 6 minutes to obtain an intermediate slurry;

[0105] (3) The intermediate slurry in step (2) is aged at 40° C. for 2 h to make it free of Co, and then washed and dried in sequence to obtain the composite catalyst.

[0106] Example 5

[0107] A composite catalyst comprises a double metal cyanide catalyst and polyethyleneimine, and the two are combined in a stable cluster form;

[0108] Among them, D of the composite catalyst at room temperature 50 The particle size is 50 μm, and the D 50 The particle size is 48 μm, D 50 The particle size change rate is 4%, and the particle size of the clusters is stable at high temperatures;

[0109] The mass ratio of the Zn element in the composite catalyst to the N element in polyethyleneimine (number average molecular weight of 3500) is 20:1;

[0110] The double metal cyanide catalyst is a Zn / Cr double metal cyanide catalyst;

[0111] The preparation method of the composite catalyst provided in this embodiment comprises the following steps:

[0112] (1) mixing zinc chloride, ethylene glycol dimethyl ether and tert-butyl alcohol in deionized water, wherein the mass ratio of zinc chloride to tert-butyl alcohol is 30:100, and the mass ratio of zinc chloride to ethylene glycol dimethyl ether is 1:10, to obtain a component A having a Zn salt content of 10% by mass;

[0113] Precursors potassium tetracyanochromate and polyethyleneimine (number average molecular weight 3500) were mixed in deionized water, the mass ratio of potassium tetracyanochromate to polyethyleneimine was 36:1, and the amount of solvent was matched according to the mass percentage of polyethyleneimine 5%, to obtain component B;

[0114] (2) adding component B obtained in step (1) to component A and mixing them for 1 min to obtain an intermediate slurry;

[0115] (3) The intermediate slurry in step (2) is aged at 40° C. for 2 h to make it Cr-free, and then washed and dried in sequence to obtain the composite catalyst.

[0116] Example 6

[0117] A composite catalyst, which differs from Example 1 only in that the mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine is 277:1, and the D 50 The particle size is 2 μm, and the D 50The particle size is 2 μm, D 50 The particle size change rate is 0%, and other materials and structures are the same as those in Example 1;

[0118] The mass ratio of potassium tetracyanochromate to polyethyleneimine in the B component in the preparation method is 500:1, and other steps and parameter controls are the same as those in Example 1.

[0119] Example 7

[0120] A composite catalyst, which differs from Example 1 only in that the number average molecular weight of polyethyleneimine is 2500, and the D 50 The particle size is 11 μm, and the D 50 The particle size is 6 μm, D 50 The particle size change rate is 45%, and other materials, structures and preparation methods are the same as those in Example 1.

[0121] Comparative Example 1

[0122] A double metal cyanide catalyst, which is different from Example 1 only in that polyethyleneimine is not added to component B, and other substances, structures and preparation methods are the same as those in Example 1.

[0123] Comparative Example 2

[0124] A catalyst, the preparation method of which comprises the following steps:

[0125] (1) mixing zinc chloride, ethylene glycol dimethyl ether, tert-butyl alcohol and polyethyleneimine (number average molecular weight of 10000) in deionized water, wherein the mass ratio of zinc chloride to tert-butyl alcohol is 3:100, and the mass ratio of zinc chloride to ethylene glycol dimethyl ether is 1:0.5, and flocculating the zinc chloride;

[0126] Potassium hexacyanocobaltate was mixed in deionized water to obtain component B, but a catalyst could not be prepared.

[0127] Comparative Example 3

[0128] A mixed catalyst, the preparation method of which comprises: following the operating steps of Example 1, the only difference is that no polyethyleneimine is added to component B, to obtain a Zn / Co double metal cyanide catalyst, and then mixing the Zn / Co double metal cyanide catalyst with polyethyleneimine having a number average molecular weight of 3000 to obtain a mixed catalyst.

[0129] Comparative Example 4

[0130] A composite catalyst, which differs from Example 1 only in that the mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine is 11:1, and the D 50The particle size is 81 μm. After high temperature treatment at 300 °C for 2 h, the D 50 The particle size is 79 μm, D 50 The particle size change rate is 2%, and other substances and structures are the same as those in Example 1; the mass ratio of potassium tetracyanochromate and polyethyleneimine in component B in the preparation method is 20:1, and other steps and parameter controls are the same as those in Example 1.

[0131] Comparative Example 5

[0132] A composite catalyst, which differs from Example 1 only in that the number average molecular weight of polyethyleneimine is 11500, and the D 50 The particle size is 13 μm, and the D 50 The particle size is 13 μm, D 50 The particle size change rate is 0%, and other materials, structures and preparation methods are the same as those in Example 1.

[0133] Comparative Example 6

[0134] A composite catalyst, which differs from Example 1 only in that the time for adding solution B to solution A is only 0.5 min, and the resulting composite catalyst has a D 50 The particle size is 104 μm. After high temperature treatment at 300 °C for 2 h, the D 50 Particle size is 101 μm, D 50 The particle size change rate is 3%, and other materials, structures and preparation methods are the same as those in Example 1.

[0135] Application Example 1

[0136] A slightly cross-linked carbon dioxide-based copolymer, the preparation method of which comprises the following steps: firstly drying a high-pressure reactor with a capacity of 100 mL in a blast oven overnight, then sequentially adding 10 mg of the composite catalyst provided in Example 1, 20 mL of propylene oxide and 40 mL of dichloromethane into the dried reactor, sealing the reactor, filling it with 30 g of carbon dioxide gas, stirring and polymerizing in a water bath for 12 hours, releasing the pressure to a normal pressure state, and taking out the product, which is the slightly cross-linked carbon dioxide-based copolymer.

[0137] Application Example 2

[0138] A slightly cross-linked carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided in Example 2 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0139] Application Example 3

[0140] A slightly cross-linked carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided in Example 3 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0141] Application Example 4

[0142] A slightly cross-linked carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided in Example 4 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0143] Application Example 5

[0144] A slightly cross-linked carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided in Example 5 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0145] Application Example 6

[0146] A slightly cross-linked carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided in Example 6 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0147] Application Example 7

[0148] A slightly cross-linked carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided in Example 7 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0149] Comparative application example 1

[0150] A carbon dioxide-based copolymer, which differs from Application Example 1 in that the double metal cyanide catalyst provided in Comparative Example 1 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0151] Comparative Application Example 2

[0152] A carbon dioxide-based copolymer. Comparative Example 2 cannot prepare a catalyst, and further cannot catalyze the carbon dioxide-based copolymer.

[0153] Comparative Application Example 3

[0154] A carbon dioxide-based copolymer, which differs from Application Example 1 in that the mixed catalyst provided in Comparative Example 3 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0155] Comparative Application Example 4

[0156] A carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided by Comparative Example 4 is used to replace the composite catalyst provided by Example 1, and other substances, amounts used and preparation methods are the same as those of Application Example 1.

[0157] Comparative Application Example 5

[0158] A carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided in Comparative Example 5 is used to replace the composite catalyst provided in Example 1, and other substances, amounts used and preparation methods are the same as those in Application Example 1.

[0159] Comparative Application Example 6

[0160] A carbon dioxide-based copolymer, which differs from Application Example 1 in that the composite catalyst provided by Comparative Example 6 is used to replace the composite catalyst provided by Example 1, and other substances, amounts used and preparation methods are the same as those of Application Example 1.

[0161] Composite catalyst appearance characterization:

[0162] The composite catalyst provided in Example 5 and the double metal cyanide catalyst provided in Comparative Example 1 were tested using a scanning electron microscope. The scanning electron microscope image of the composite catalyst provided in Example 5 was obtained. Figure 2 As shown, the scanning electron microscope image of the double metal cyanide catalyst provided in Comparative Example 1 is as shown Figure 3 As shown;

[0163] Start with Figure 2 It can be seen that the addition of polyethyleneimine can aggregate with the double metal cyanide catalyst particles to form clusters.

[0164] Then from Figure 3 It can be seen that the double metal cyanide catalyst itself has not undergone obvious aggregation, but the size is not uniform, which may be due to the fast complexation reaction rate causing the uneven particle size.

[0165] Thermal stability of composite catalyst:

[0166] The thermal gravimetric temperature of the sample at a weight loss of 5 wt% was measured using TA's TGA 550 model. The test atmosphere was N2. The heating program was: from room temperature to 600°C at a heating rate of 10°C / min. The thermal gravimetric temperature at a weight loss of 5 wt% was read and recorded as the thermal decomposition temperature.

[0167] The carbon dioxide-based copolymers provided in Examples 1 to 7 and Comparative Examples 1 to 6 were tested under the conditions of heating from room temperature to 600°C, a heating rate of 10°C / min, and a nitrogen atmosphere. The test results are shown in Table 1:

[0168] Table 1

[0169] Thermal decomposition temperature / ℃ Application Example 1 284 Application Example 2 293 Application Example 3 290 Application Example 4 289 Application Example 5 298 Application Example 6 265 Application Example 7 271 Comparative application example 1 262 Comparative Application Example 2 / Comparative Application Example 3 260 Comparative Application Example 4 Aggregation failure Comparative Application Example 5 Aggregation failure Comparative Application Example 6 Aggregation failure

[0170] Note: “ / ” indicates that the experiment was not performed.

[0171] From the data in Table 1, we can see that:

[0172] (1) The slightly cross-linked carbon dioxide-based copolymers provided in Application Examples 1 to 5 all have excellent thermal stability, with thermal decomposition temperatures as high as 284 to 298°C.

[0173] (2) The carbon dioxide-based copolymer provided in Comparative Application Example 1 uses a double metal cyanide catalyst, which results in the inability to form a micro-crosslinked structure in the obtained carbon dioxide-based copolymer, and thus has poor thermal stability;

[0174] Comparative Application Example 2: Adding polyethyleneimine to component A will directly cause flocculation, and the catalyst cannot be prepared, and further, the carbon dioxide-based copolymer cannot be prepared;

[0175] The carbon dioxide-based copolymer provided in Comparative Application Example 3 uses a mixture of a double metal cyanide catalyst and polyethyleneimine, resulting in the obtained carbon dioxide-based copolymer only polymerizing on the surface of the double metal cyanide catalyst, and the addition of polyethyleneimine has a certain effect on the activity of the double metal cyanide catalyst, thereby failing to obtain a carbon dioxide-based copolymer with a physical micro-crosslinking structure, resulting in poor thermal stability of the carbon dioxide-based copolymer;

[0176] In the comparative application example 4, the mass ratio of the Zn element to the N element from the polyethyleneimine in the composite catalyst is too low, resulting in an excessively large particle size of the composite catalyst, so that relatively more double metal cyanide catalysts in the obtained composite catalyst are wrapped inside the clusters. This part of the wrapped double metal cyanide catalyst is difficult to contact with the monomer during polymerization and cannot catalyze the reaction, thereby causing polymerization failure.

[0177] The molecular weight of polyethyleneimine in the composite catalyst used in comparative application example 5 is too high, resulting in too many initiation sites of the double metal cyanide catalyst being occupied by polyethyleneimine, making it difficult to initiate the PPC polymerization reaction, and even leading to polymerization failure;

[0178] In the composite catalyst used in comparative application example 6, the time used for adding component B to component A during preparation is too short, which will result in the D 50 When the particle size is too large, relatively more double metal cyanide catalysts in the obtained composite catalyst are encapsulated inside the clusters. During polymerization, this part of the encapsulated double metal cyanide catalysts is difficult to contact with the monomers and cannot catalyze the reaction, thereby causing polymerization failure.

[0179] (3) Compared with Application Example 1, the mass ratio of the Zn element to the N element from polyethyleneimine in the composite catalyst used in Application Example 6 is too high, resulting in a too small particle size of the composite catalyst. When used to catalyze a carbon dioxide-based copolymer, the micro-crosslinking degree of the obtained carbon dioxide-based copolymer is insufficient, and thus the thermal stability is poor;

[0180] The molecular weight of polyethyleneimine in the composite catalyst used in Application Example 7 is too low, resulting in too few sites for polyethyleneimine to complex with the double metal cyanide catalyst, which in turn leads to poor thermal stability of the formed composite catalyst and poor thermal stability of the carbon dioxide-based copolymer catalyzed by it.

[0181] The applicant declares that the present invention illustrates a composite catalyst and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite catalyst, characterized in that: The composite catalyst comprises a double metal cyanide catalyst and polyethyleneimine, and the two are combined in a stable cluster form; The double metal cyanide catalyst contains Zn element.

2. The composite catalyst according to claim 1, characterized in that The mass ratio of the Zn element in the composite catalyst to the N element from polyethyleneimine is (20-100):

1.

3. The composite catalyst according to claim 1 or 2, characterized in that The D 50 The particle size is 12~50μm.

4. The composite catalyst according to any one of claims 1 to 3, characterized in that The number average molecular weight of the polyethyleneimine is 3000-10000.

5. A method for preparing a composite catalyst, characterized in that: The preparation method comprises the following steps: (1) mixing Zn salt, organic ligand and tert-butyl alcohol in water to obtain component A; Mixing a double metal cyanide catalyst precursor and polyethyleneimine in water to obtain a component B; (2) adding the component B obtained in step (1) into the component A for mixing, and subjecting the mixture to aging, washing and drying to obtain the composite catalyst.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the Zn salt to tert-butyl alcohol is (3-30):100; The mass ratio of the Zn salt to the organic ligand is 1:(0.5-10); Preferably, the mass percentage of Zn salt in the component A is 1-10%.

7. The preparation method according to claim 5 or 6, characterized in that: The mass ratio of the double metal cyanide catalyst precursor to polyethyleneimine is (10-100):1; Preferably, the number average molecular weight of the polyethyleneimine is 3000-10000.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The mass percentage of polyethyleneimine in the B component is 0.1-5%.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The time for adding component B obtained in step (1) into component A for mixing is ≥1 min.

10. A slightly cross-linked carbon dioxide-based copolymer, characterized in that: The slightly cross-linked carbon dioxide-based copolymer is prepared using at least one of the composite catalysts described in any one of claims 1 to 4 or the composite catalysts prepared by the preparation method described in any one of claims 5 to 9 as a catalyst.